PENDAMPINGAN PEMANTAUAN PERTUMBUHAN MELALUI PENGUKURAN STATUS GIZI ANAK SEKOLAH DASAR DI BULOTADAA BARAT - Pomatahu, Aisah R; Pauweni, Mirdayani (Universitas Negeri Gorontalo, 2024)
The primary school age period is called midle childhood, which is the period of children after toddlers who have about 6-12 years. In this period, tremendous cognitive, emotional and social development occurs, but on the one hand the rate and speed of growth is relatively fixed. Therefore, periodic growth monitoring is required during childhood. The purpose of this activity is to monitor the growth of primary school children in Bulotadaa Barat, and provide secondary data on child growth. Based on the evaluation of the activity, it can be concluded that it has been carried out according to the stages of the activity, namely the preparation stage, the implementation stage, and the results stage. The objectives of this activity were achieved, including the availability of child growth data as secondary data in schools.